Molecular Imprinted Based Quartz Crystal Microbalance Nanosensors for Mercury Detection - Sabina Hüseynli; Duygu Çimen; Nilay Bereli; Adil Denizli (Global Challenges, 2019)
Abstract Mercury(II) ions are emerging as a result of more human activity, especially coal‐fired power plants, industrial processes, waste incineration plants, and mining. The mercury found in different forms after spreading around diffuses the nature of other living things. Although the damage to health is not yet clear, it is obvious that it is the cause of many diseases. This work detects the problem of mercury(II) ions, one of the active pollutants in wastewater. For this purpose, it is possible to detect the smallest amount of mercury(II) ions by means of the mercury(II) ions suppressed quartz crystal microbalance nanosensor developed. Zinc(II) and cadmium(II) ions are chosen as competitor elements. Developed nanosensor technology is known as the ideal method in the laboratory environment to detect mercury(II) ions from wastewater because of its low cost and precise result orientation. The range of linearity and the limit of detection are measured as 0.25 × 10−9–50 × 10−9 m. The detection limit is found to be 0.21 × 10−9 m. The mercury(II) ions imprinted nanosensors prepared according to the obtained experimental findings show high selectivity and sensitivity to detect mercury(II) ions from wastewater.